2021
DOI: 10.1051/e3sconf/202130403010
|View full text |Cite
|
Sign up to set email alerts
|

Study on technological properties of winter wheat soils

Abstract: The aim of the study is to study and analyze the physical, mechanical and technological properties of soils from under winter grain crops in the hot climate of Uzbekistan. The results of determining the moisture content, density, hardness and resistance to various deformations of soils after harvesting winter wheat are presented. The basic principles and methods of classical mechanics, mathematical analysis and statistics were used in this study. Studies have found that, in the layer 0-30, the soil moisture fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Based on the analysis of the conducted research work, the use of slope field processing and grain sowing technologies and technical tools in developed countries, as well as the requirements of agrotechnical for grain planting, a combined machine for processing and sowing grain on sloped Fields was developed [3,4,7].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the analysis of the conducted research work, the use of slope field processing and grain sowing technologies and technical tools in developed countries, as well as the requirements of agrotechnical for grain planting, a combined machine for processing and sowing grain on sloped Fields was developed [3,4,7].…”
Section: Methodsmentioning
confidence: 99%
“…Analysis of research has shown that prevention of water erosion during seeding of grain crops on sloping fields and conservation of moisture in the soil, as well as reduction of fuel, labor, and material costs, can be achieved by applying technologies of soil treatment with simultaneous seeding of grain seeds and formation of anti-water erosion ridges and machines for its implementation [3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Uzbekistan is one of the leading countries in the world in the production of melon products and especially valuable varieties of melons, which are famous for their taste qualities not only in our country but also far beyond its borders [1][2][3][4]. Therefore, it is necessary to increase the production volume of melons.…”
Section: Introductionmentioning
confidence: 99%
“…To do this, it is necessary that when the soil interacts with the elements of the slitter, its vertical movement prevails. The well-known works, D. Chuyanov [1][2], F. Mamatov , B. Mirzaev [4-7, 12-19, 21, 23, 26], K. Ravshanov [9,22,25,28,33], U. Kodirov [1,21,28,33], I. Temirov [9,11,33], on substantiating the parameters of plow hulls, are mainly aimed at studying the process of lifting and complete rotation of the formation, in which horizontal soil movement prevails. Studies of moving the soil along the oblique blade have been carried out.…”
Section: Introductionmentioning
confidence: 99%